Engineered disorder and light propagation in a planar photonic glass - Romanov, Sergey; Orlov, Sergej; Ploss, Daniel; Weiss, Clemens K.; Vogel, Nicolas; Peschel, Ulf (Scientific Reports, 2016)
The interaction of light with matter strongly depends on the structure of the latter at wavelength scale. Ordered systems interact with light via collective modes, giving rise to diffraction. In contrast, completely disordered systems are dominated by Mie resonances of individual particles and random scattering. However, less clear is the transition regime in between these two extremes, where diffraction, Mie resonances and near-field interaction between individual scatterers interplay. Here, we probe this transitional regime by creating colloidal crystals with controlled disorder from two-dimensional self-assembly of bidisperse spheres. Choosing the particle size in a way that the small particles are transparent in the spectral region of interest enables us to probe in detail the effect of increasing positional disorder on the optical properties of the large spheres. With increasing disorder a transition from a collective optical response characterized by diffractive resonances to single particles scattering represented by Mie resonances occurs. In between these extremes, we identify an intermediate, hopping-like light transport regime mediated by resonant interactions between individual spheres. These results suggest that different levels of disorder, characterized not only by absence of long range order but also by differences in short-range correlation and interparticle distance, exist in colloidal glasses.

Experimental cross-polarization detection of coupling far-field light to highly confined plasmonic gap modes via nanoantennas - Wen, J.; Banzer, Peter; Kriesch, Arian; Ploss, Daniel; Schmauß, Bernhard; Peschel, Ulf (Applied Physics Letters, 2011)
We experimentally demonstrate the coupling of far-field light to highly confined plasmonic gap modes via connected nanoantennas. The excitation of plasmonic gap modes is shown to depend on the polarization, position, and wavelength of the incident beam. Far-field measurements performed in crossed polarization allow for the detection of extremely weak signals re-emitted from gap waveguides and can increase the signal-to-noise ratio dramatically.
lhft_intern.bib::Wen11

Functional Plasmonic Nanocircuits with Low Insertion and Propagation Losses - Kriesch, Arian; Burgos, Stanley P.; Ploss, Daniel; Pfeifer, Hannes; Atwater, Harry A.; Peschel, Ulf (Nano Letters, 2013)
We experimentally demonstrate plasmonic nanocircuits operating as subdiffraction directional couplers optically excited with high efficiency from free-space using optical Yagi-Uda style antennas at extgreekl0 = 1550 nm. The optical Yagi-Uda style antennas are designed to feed channel plasmon waveguides with high efficiency (45% in coupling, 60% total emission), narrow angular directivity (<40°), and low insertion loss. SPP channel waveguides exhibit propagation lengths as large as 34 extgreekmm with adiabatically tuned confinement and are integrated with ultracompact (5 × 10 extgreekmm2), highly dispersive directional couplers, which enable 30 dB discrimination over extgreekDl = 200 nm with only 0.3 dB device loss.
EAM Import::2019-03-14

Generation and subwavelength focusing of longitudinal magnetic fields in a metallized fiber tip - Ploss, Daniel; Kriesch, Arian; Pfeifer, Hannes; Banzer, Peter; Peschel, Ulf (Optics Express, 2014)
We demonstrate experimentally and numerically that in fiber tips as they are used in NSOMs azimuthally polarized electrical fields (|Eazi|2 / |Etot|2 ≈55% ± 5% for extgreekl0= 1550 nm), respectively subwavelength confined (FWHM ≈450 nm ≈ extgreekl0/3.5) magnetic fields, are generated for a certain tip aperture diameter (d = 1.4 extgreekmm). We attribute the generation of this field distribution in metal-coated fiber tips to symmetry breaking in the bend and subsequent plasmonic mode filtering in the truncated conical taper.
EAM Import::2019-03-13

Investigating plasmonic gap modes coupled to nanoantennas - Wen, J.; Kriesch, Arian; Ploss, Daniel; Banzer, Peter; Schmauß, Bernhard; Peschel, Ulf (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Wen2011

Measuring the Kerr-nonlinearity of Ag in plasmonic nano-circuits - Kriesch, Arian; Pfeifer, Hannes; Burgos, Stanley P.; Ploss, Daniel; Banzer, Peter; Atwater, Harry A.; Peschel, Ulf (Nonlinear Optics 2013, 2013)
We observe nonlinear switching of ultrashort (600fs) laser pulses in subwavelength plasmonic nanocircuits. This allows us to experimentally determine the third-order nonlinear coefficient of silver.
EAM Import::2019-03-12

Near-Field Analysis of Bright and Dark Modes on Plasmonic Metasurfaces Showing Extraordinary Suppressed Transmission - Dobmann, Sabine; Kriesch, Arian; Ploss, Daniel; Peschel, Ulf (Advanced Optical Materials, 2014)
Plasmonic metasurfaces are investigated that consist of a sub-wavelength line pattern in an ultrathin ( 10 nm) silver film, designed for extraordinary suppressed transmission (EOST) in the visible spectral range. Measurements with a near-field scanning optical microscope (NSOM) demonstrate that farfield irradiation resonantly excites antenna-like (bright) modes that are localized on the metal ridges. The re-radiation of these modes into the far-field interferes destructively with the transmitted wave, thus suppressing transmission almost completely. In contrast, a second type of mode, bound (dark) surface plasmon polaritons (SPPs) launched from an NSOM tip, propagates well across the metasurface, preferentially perpendicular to the grating lines.
EAM Import::2019-03-12

Polarization features of optically pumped CdS nanowire lasers - Roeder, Robert; Ploss, Daniel; Kriesch, Arian; Buschlinger, Robert; Geburt, Sebastian; Peschel, Ulf; Ronning, Carsten (Journal of Physics D-Applied Physics, 2014)
High quality CdS nanowires suspended in air were optically pumped both below and above the lasing threshold. The polarization of the pump laser was varied while emission out of the end facet of the nanowire was monitored in a `head-on' measurement geometry. Highest pump-efficiency and most efficient absorption of the pump radiation are demonstrated for an incident electric field being polarized parallel to the nanowire axis. This polarization dependence, which was observed both above the lasing threshold and in the regime of amplified spontaneous emission, is caused by an enhanced absorption for parallel polarized optical pumping. Measured Stokes parameters of the nanowire emission reveal that due to the onset of lasing the degree of polarization rapidly increases from approximately 15 to 85%. Both Stokes parameters and degree of polarization of the nanowire lasing emission are independent of the excitation polarization. The transversal lasing mode is therefore not notably affected by the polarization of the pumping beam, although the supply with optical gain is significantly enhanced for an excitation polarization parallel to the nanowire axis.
EAM Import::2019-03-08

Young's Double-Slit, Invisible Objects and the Role of Noise in an Optical Epsilon-near-Zero Experiment - Ploss, Daniel; Kriesch, Arian; Etrich, Christoph; Engheta, Nader; Peschel, Ulf (ACS Photonics, 2017)
Epsilon-near-zero (ENZ) media disclose the peculiarities of electrodynamics in the limit of infinite wavelength but nonzero frequency for experiments and applications. Theory suggests that wave interaction with obstacles and disturbances dramatically changes in this domain. To investigate the optics of those effects, we fabricated a nanostructured 2D optical ENZ multilayer waveguide that is probed with wavelength-tuned laser light via a nanoscale wave launch configuration. In this experimental framework, we directly optically measure wave propagation and diffraction in a realistic system with the level and scale of imperfection that is typical in nanooptics. As we scan the wavelength from 1.0 to 1.7 μm, we approach the ENZ regime and observe the interference pattern of a microscale Young's double slit to steeply diverge. By evaluating multiple diffraction orders we experimentally determine the effective refractive index neff and its zero-crossing as an intrinsic measured reference, which is in agreement with theoretical predictions. We further verify that the double-slit and specifically placed scattering objects become gradually invisible when approaching the ENZ regime. We also observe that light-matter interaction intensifies toward ENZ and quantify how speckle noise, caused by tiny random imperfections, increasingly dominates the optical response and blue-shifts the cutoff frequency.
CRIS-Team Scopus Importer:2023-04-20
Keywords: diffraction; double-slit; ENZ; epsilon-near-zero; noise; photonics